Nada Nusantara: transcending cultural boundaries through transcultural music compositions - Salleh, Marzelan; Williams, Alan; Mohamed Razali, Camellia Siti Maya; Rachman, Abdul; Sejati, Irfanda Rizki Harmono (Universidade Federal de Goias, 2026)
Nada Nusantara is a collective of composers and musicians dedicated to exploring the musical heritage of the Nusantara (Malay Archipelago) and fusing it with classical Western traditions. Through original transcultural compositions, the group seeks to blend diverse musical forms, melodies, rhythms, and instruments from these traditions, creating a soundscape that intertwines emotional depth with physical expression. Their music fosters meaningful cultural connections and redefines contemporary practices by bridging oral and notated traditions. This study analyzes two representative works—Cermin Edina by Marzelan Salleh and Menambat Rakit by Camellia Razali—to examine Nada Nusantara’s approach to transcultural composition. Cermin Edina reflects a rich interweaving of gamelan-inspired rhythmic patterns with Western harmonic language, employing cyclical structures, vocal ornamentation, and modal shifts that evoke a meditative yet theatrical atmosphere. In contrast, Menambat Rakit draws on the timbral qualities of traditional Malay music and integrates them with Western harmonic textures, producing a contemplative narrative through layered textures and dynamic contrasts. These analyses highlight how the composers thoughtfully incorporate elements from both cultures, resulting in works that are structurally and expressively transcultural. Nada Nusantara plays a vital role in promoting cultural sustainability and diversity through international collaborations and artistic innovation. Their compositions demonstrate the universality of music and its power to transcend cultural boundaries. By spotlighting the artistic and aesthetic values of Nusantara culture, Nada Nusantara advances transcultural music as a contemporary art form, embracing openness, creativity, and the limitless possibilities of cultural fusion in today’s global musical landscape.